(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The purpose of this paper is to show the application of a new methodology approach to diagnose the impact of management of Information and Communication Technologies (ICT) with the reference frame ISO/IEC 38500 inside the organizations. It is based on the government's analysis of organization’s technological resource management, being the strategic axis part of business strategic planning and its ICT Governance, effectiveness and efficiency, and the value of ICT for its guidelines and the risks involved in its development to optimize the use of organization’s resources. In the first stage, a documentary research was carried out as an essential part of this study and an interview with an expert; Then a tool (questionnaire) was designed to collect, measure and evaluate data on aspects and components of the ISO/IEC 38500 standard. A case study of Ecuadorian retail organization was carried out. Once the information was processed, the respective indicators were obtained that helped to identify current status of ICT governance processes of the organization. With the obtained indicators we could see which principles are the ones that characterize this sector, in which they put the greatest amount of resources; be they human or financial. It was also evident that the two dimensions on which the study was based on have very different results, since emphasis was placed on what corresponds.